OPTIMALISASI MANAJEMEN KEUANGAN BERBASIS DIGITAL SI APIK SEBAGAI PENINGKATAN MUTU UMKM - Retnowati, May Shinta; Kusumastuti, Anisa Silvi; Rafifahnur, Nisrina (FACULTY OF ECONOMICS AND BUSINESS FLORES UNIVERSITY, 2024)
Micro, small and medium enterprises (MSMEs) are one of the drivers of the Indonesian economy. Along with the times and technology, it causes business actors to develop more in all respects, especially finance. One of the most important parts of a business is good financial records. Business actors who do not have neat and correct finances will experience a little difficulty in applying for capital or credit to banks. The lack of education and understanding they have can also be one of the causes. With this problem in mind, the government collaborated with Bank Indonesia to create a financial recording application to assist business actors in reporting their finances, namely the Si Apik application. The purpose of this writing is to find out how Si Apik's role is in optimizing the MSME financial administration so that they can have neat financial reports. The method used is to use a literature review from various sources that examines the understanding of the Si Apik application utilization. The results of the research show that preparedness has an important role in the development of MSME financial accounting literacy. However, the lack of public understanding of this application causes few users. With this, there must be socialization and training that must be carried out by the government and parties who already know how to use the Si Apik application